Strategy for Empowering Forest Farmer Groups (KTH) Around the Sawala-Mandapa Kadipaten Training Forest, Majalengka, West Java - Ian Maryana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research is based on the substance of maintaining the existence, empowerment, and development of Forest Farmers Groups (KTH). The purpose of the research is to obtain a KTH empowerment strategy, the type of training needed, and the development of its program of activities. The research method used is descriptive qualitative which is carried out through case studies in the Sawala-Mandapa Education and Training Forest in the Kadipaten, Majalengka Regency, West Java Province. The results show that the KTH empowerment strategy, which is based on theory, is carried out through four stages of development, it is necessary to add three stages, namely: asset development, regional management development, relationship development so that it becomes seven stages. The most appropriate empowerment strategy based on this research is the regional management development strategy and business development strategy. The new types of training obtained are: Area Management Training, and Training on Processing and Marketing of Forestry Farm Products. In order for KTH to develop its program of activities, the six stages that have been stated by experts need to be added to two stages, namely: Development Planning Phase, and Monitoring Phase.